CHALLENGES IN TEACHING THE NEW ENGLISH TEXTBOOKS: A CASE STUDY AT NGUYEN TAT THANH SECONDARY SCHOOL = THÁCH THỨC TRONG VIỆC DẠY BỘ SÁCH GIÁO KHOA TIẾNG ANH MỚI: NGHIÊN CỨU TRƯỜNG HỢP TẠI TRƯỜNG THCS NGUYỄN TẤT THÀNH - Ngụy, Việt Hưng (2020)
In 2012, the Ministry of Education and Training passed an Official Dispatch for a new set of English textbooks to be piloted in several schools in Vietnam, including Nguyen Tat Thanh secondary school. These textbooks focus on developing students’ communicative competence and thus requiring teachers to adapt to the communicative language teaching method. The aims of this study are to find out the evaluation of the new textbooks from teachers at Nguyen Tat Thanh secondary school and to see the challenges that they face when following the new English program and the new textbooks. Subsequent to this, suggestions for improvements of the pilot textbooks are to be proposed. Questionnaires in the form of an evaluation checklist were given to the 8 teachers in Nguyen Tat Thanh secondary school, and were followed by semi-structured interviews. In this study, the participants praised the new textbooks for the focus on communication, the diversity in topics, the new tasks, and the spiral structure. On the other hand, they criticized the books for the difficulty of language knowledge, the unsatisfactory design of some exercises, particularly the Looking back section, and the lack of representation of the target language’s culture. The teachers encounter challenges with the unfamiliar topics, students’ level gap, and lack of class time. The result of this study provides insight into the direct experience of the teachers who work with the new textbooks.